Examining the Utilization and Impact of Teaching Resources on Biology Education in Awka South Local Government Area, Nigeria - Tochukwu Ebuka Umeohana (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Objective: This study investigates the use of teaching resources and their impact on the quality of Biology education in secondary schools within the Awka South Local Government Area. Method: A descriptive survey design was adopted to gather teacher and student data. A random sampling technique was used to select 38 Biology teachers. Data collection was facilitated using a self-structured 4-point rating scale questionnaire comprising personal information and items related to the study objectives. Descriptive statistics were used to analyze the data, particularly focusing on the frequency and extent of teaching resource utilization. Result: The study found varied levels of teaching resource utilization among Biology teachers. Traditional teaching tools such as audio and video recorders, projectors, and microphones were used to a limited extent. In contrast, more innovative resources like organ tissue specimens and multimedia aids were more widely employed. It was also found that consistent use of teaching resources improves students’ understanding of complex Biology concepts and increases their interest and competence in the subject. Additionally, the integration of ICT supports students in accessing current and relevant information. Conclusion: The findings highlight the critical role of teaching resources particularly modern and ICT-based tools in enhancing student engagement, comprehension, and academic performance in Biology. The level of effectiveness largely depends on the type and consistency of teacher resource usage. Contribution: This study provides valuable insights for school administrators and educational policymakers on the importance of resource allocation and teacher training. It recommends equipping educators with adequate training and access to effective teaching aids to promote improved Biology education outcomes in the Awka South Local Government Area.